SOSIALISASI PENYELESAIAN PERMASALAHAN UTANG PIUTANG DI KELURAHAN KENARI, JAKARTA PUSAT - Bernadete Nurmawati; Hudi Yusuf; Rinaldi Agusta Fahlevie (LPPM Institut Pendidikan Nusantara Global, 2025)
The issue of debt and credit is a part of civil legal relations that often leads to disputes within society, primarily due to a lack of understanding of legal aspects and available resolution mechanisms. This Community Service (PkM) activity was conducted in Kenari Subdistrict, Central Jakarta, with the aim of providing legal education regarding debt agreements from both civil and criminal law perspectives. The materials delivered included the basic concepts of debt and credit, types of loan agreements according to the Indonesian Civil Code (KUH Perdata), the legal requirements for valid agreements as outlined in Article 1320 of the Civil Code, and the importance of written evidence in lending transactions. Additionally, participants were informed about the legal risks involved, both in cases of breach of contract and when criminal elements such as fraud (Article 378 of the Criminal Code) or embezzlement (Article 372 of the Criminal Code) are present. Through an interactive and practical approach, this activity successfully enhanced public legal awareness regarding their rights and obligations in civil relations, and introduced alternative non-litigation dispute resolution methods such as mediation and deliberation. The participants’ enthusiasm indicated that legal education is highly necessary and relevant to everyday issues. This initiative is expected to serve as a sustainable first step toward building a more legally aware society, capable of conducting legitimate and secure transactions, and resolving disputes wisely in accordance with applicable laws.